2014
DOI: 10.1063/1.4864648
|View full text |Cite
|
Sign up to set email alerts
|

Hysteretic electrical transport in BaTiO3/Ba1−xSrxTiO3/Ge heterostructures

Abstract: We present electrical transport measurements of heterostructures comprised of BaTiO 3 and Ba 1−x Sr x TiO 3 epitaxially grown on Ge. The Sr-alloying imparts compressive strain to the BaTiO 3 , which enables the thermal expansion mismatch between BaTiO 3 and Ge to be overcome to achieve c-axis oriented growth. The conduction bands of BaTiO 3 and Ba 1−x Sr x TiO 3 are nearly aligned with the conduction band of Ge, which facilitates electron transport. Electrical transport measurements through the dielectric stac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 23 publications
1
27
0
2
Order By: Relevance
“…Ngai et al [115] have grown a 20 nm tri-layer Ba 1− x Sr x TiO 3 stack—with decreasing x values—as a buffer and have obtained c -axis oriented 40 nm thick BaTiO 3 films. The in-plane and out-of-plane parameters were 3.987 Å and 4.040 Å respectively.…”
Section: Mbe Of Batio3 On Semiconductors: Growth and Crystalline Strumentioning
confidence: 99%
See 4 more Smart Citations
“…Ngai et al [115] have grown a 20 nm tri-layer Ba 1− x Sr x TiO 3 stack—with decreasing x values—as a buffer and have obtained c -axis oriented 40 nm thick BaTiO 3 films. The in-plane and out-of-plane parameters were 3.987 Å and 4.040 Å respectively.…”
Section: Mbe Of Batio3 On Semiconductors: Growth and Crystalline Strumentioning
confidence: 99%
“…The lattice parameters were a = 3.96 Å and c = 4.06 Å for 16 nm thick BaTiO 3 . Both in [115] and [116], the comparison of the x-ray diffraction θ /2 θ scans clearly showed the impact of the buffer insertion on the BaTiO 3 crystalline orientation. In the work of Ponath et al [116], STEM-HAADF images revealed that Ti atomic columns close to the top of the BaTiO 3 film are shifted downward from the cell center, meaning a ‘down’ polarization, which is in good agreement with their DFT calculations.…”
Section: Mbe Of Batio3 On Semiconductors: Growth and Crystalline Strumentioning
confidence: 99%
See 3 more Smart Citations